Measuring the impact of intellectual capital in accounting on developing the capabilities of university students, field research at Bukan University - Ahmed, Rizkar Ali; Muradi, Afsar Ali (Al-Ghary Journal of Economic and Administrative Sciences, 2018)
Intellectual capital aspects such as human capital, structural capital and customer capital are important variables of the whole intellectual capital management programmed, which forms part of the knowledge management initiatives of institutes of higher learning. The skills and expertise of university staff as part of its human capital are discussed. Structural capital will encompass aspects such as the role of innovation and intellectual property rights. Customer capital of the university and the knowledge of stakeholders in the field of tertiary education are becoming more important. The results of a study done at aUniversityofHuman Developmentare used to indicate which of these aspects needs to be measured and a new framework for measurement Intellectual capital. Skills, creativity, values and culture are among affecting factors which are a great consensus on the importance of intangible assets as a source of economic competition for educational institutions. However, it was not possible to develop reliable measures to measure these assets, but the intellectual capital of the institution and its management becomes a competitive advantage for enterprises that requires new talent to measure these intangible assets